Self-localization System for Wireless Sensor Network - Martusevičius, V.; Kazanavičius, E. (Elektronika ir Elektrotechnika, 2010)
Wireless sensor networks (WSNs) consist of many small battery powered nodes with wireless communication and sensing capabilities. This type of network has many possible applications in the scientific, military and commercial domains. Examples of these applications include environmental monitoring, surveillance and many others. Despite the fact that the main goal of the WSN is to monitor an area of interest, several primary objectives have to be achieved. The definition of self-localization system is one of these prerequisites required to make functional many of WSN applications that rely on location information. Therefore, we propose a self-localization system that is the ability of the nodes to self-conFig. among themselves to form a relative coordinate system. This system includes a special method that increases the longevity of the self-localization system according to changing energy situation in a dynamic WSN.